Study on the synergistic evolution of environment and industry-a case study of provinces along the yellow river basin - Wang, Liangmin; Wei, Hongyi; Luo, Wentong; Xue, Weixian (Frontiers in Environmental Science, 2024)
The ecological protection and high-quality development of the provinces along the Yellow River Basin have become a major national strategy in China. However, the synergistic development of the environment and industry within the basin still faces numerous challenges. Research studies on the synergistic evolution of industry with the environment are important to guide future development of the provinces. This paper combines panel data from eight provinces in the Yellow River Basin from 2011 to 2020, utilizes the Entropy Weight TOPSIS method to evaluate the growth index of subsystems, and then employs the L-V model to measure the interaction force and synergistic degree of the environmental and industrial subsystems in the provinces along the Yellow River Basin. Finally, it simulates the synergistic evolution paths of each province under different scenarios. The study shows that: 1. From 2011 to 2020, the synergy effects in the upper and middle reaches of the Yellow River Basin exhibited an upward trend, while the synergy effects in the lower reaches demonstrated a downward trend. In the upper reaches, the shift was from mild non-synergy to mild synergy, in the middle reaches from mild non-synergy to strong synergy, and in the lower reaches from strong synergy to strong non-synergy. 2. The development model in the upper and middle reaches transitioned from a weakly beneficial relationship between industry and the environment to a mutually beneficial symbiotic model. In contrast, the lower reaches shifted from a mutually beneficial symbiotic model to a state of weak industrial benefits and strong environmental harm, ultimately reaching a state where both industry and the environment mutually harmed each other. 3. According to the forecast of industrial and environmental synergy for the next 30 years, Qinghai, Inner Mongolia, Ningxia, and Shanxi provinces would benefit the most from adopting a mutually beneficial symbiotic model. However, as the development of a symbiotic model requires more external support and incurs higher costs, it is essential for each province to select its development model based on its own economic conditions. Based on this, this paper provides a theoretical basis for the development of the environment and industry in the provinces along the Yellow River Basin.